MODERN REQUIREMENTS FOR A COACH-TEACHER IN CHILDREN'S AND YOUTH SPORTS (Physical Culture and Sport: Scientific Perspective, 2024)
In today's world, dynamic changes in all spheres of life create new challenges for physical education and sports professionals. The development of science, technology, medicine and the popularity of a healthy lifestyle determine the need to train competent and multifunctional specialists. They should combine knowledge of pedagogy, psychology, innovative training methods, medical support and modern technologies.The article analyses the peculiarities of training future specialists in higher education institutions, including theoretical, methodological, practical and reflective components. Theoretical training provides knowledge of the fundamentals of science, methodological training - development of pedagogical skills, practical training - consolidation of skills in real conditions, and reflective training helps to assess the compliance of their own qualities with professional requirements. Special attention is paid to key competencies: organisational, design, prognostic and constructive. These skills allow professionals to effectively plan, implement and improve physical education and sports activities.The importance of continuous self-improvement of trainers-teachers through courses, trainings, and research is also emphasised. The ethical, communicative, intellectual and psychomotor qualities of specialists are also important. The ability to make prompt decisions, maintain a high level of physical fitness, demonstrate pedagogical tact and adhere to ethical standards that determine the professional level of a coach.The article also focuses on the formation of a positive image of specialists, which includes general cultural competence, business style of communication and an example for students. Thus, a future specialist in the field of physical education is a person who is able to adapt to modern challenges and ensure the effectiveness of physical education.
Keywords: coach-teacher; children's and youth sports; professional training; professional qualities